Freeze-Drying Spermatozoa as an Alternative Method for Rescuing Genetic Material of Animal - Takdir Saili (Indonesian Center for Animal Research and Development, 2008)
Cryopreservation is one of the commonly methods used in spermatozoa preservation in which sperm is frozen and stored in the container of liquid nitrogen. The frozen sperm is still motile after thawing, so it is possible to use it in both artificial insemination and in vitro fertilization to produce an embryo. However, this technique needs a continuous supply of liquid nitrogen and a container as a place to store the frozen sperm. The advanced technique in microinjection has led the possibility of using immotile sperm to fertilize oocyte. Therefore, the sperm preservation method may be simplified because the motility of sperm has not been taken into consideration in fertilization compared to the previous method. Freeze-drying sperm is the proposed method in which the sperm is frozen and sublimated using freeze-drying machine to produce freeze-dried sperm. The freeze-dried sperm might be stored in room temperature or in refrigerator. Several reports have claimed that freeze-dried sperm is not motile but it still has capability to fertilize oocyte, even produces offspring, because its DNA remains intact. Key words: Cryopreservation, freeze-drying, sperm, oocyte